A Right to Housing: Foundation for a New Social Agenda - Bratt, Rachel G.; Stone, Michael Eric; Hartman, Chester W. (Temple University Press, 2006)
In the 1949 Housing Act, Congress declared "a decent home and a suitable living environment for every American family" our national housing goal. Today, little more than half a century later, upwards of 100 million people in the United States live in housing that is physically inadequate, unsafe, overcrowded, or unaffordable.The contributors toA Right to Housingconsider the key issues related to America's housing crisis, including income inequality and insecurity, segregation and discrimination, the rights of the elderly, as well as legislative and judicial responses to homelessness. The book offers a detailed examination of how access to adequate housing is directly related to economic security.With essays by leading activists and scholars, this book presents a powerful and compelling analysis of the persistent inability of the U.S. to meet many of its citizens' housing needs, and a comprehensive proposal for progressive change.